Application of building information modeling (BIM) in hydrotechnics - Taseski, Goce; Duska Sofronievska Milokva; Nikola Krstovski (Macedonian Committee on Large Dams, 2024)
Traditionally, project documentation is produced in two-dimensional graphical presentation with the aid of computer software. This approach is time-consuming and of low efficiency. Building Information Modeling is an advanced technology that is the basis of digital transformation in the AEC industry. BIM represents an innovative process based on an unambiguous 3D model that allows clear visualization and offers tools for more efficient planning, design, construction and management of construction facilities. The aim of the paper is to emphasize the benefits of the application of BIM in hydrotechnical projects, with a special reference to the benefits obtained from the design based on BIM technology. By presenting the basics of the concept of Information Modeling of buildings and through practical modeling of hydrotechnical facilities.
Keywords: Hydrotechnical facilities, Building Information Modeling